Les ruses de l’intendance administrative. Exemple de la statistique de l’absentéisme scolaire - Arlette Meunier (Cahiers de la Recherche sur l'Education et les Savoirs)
This paper analyses the measure of a population said to be at risk, and how absenteeism is reported officially. The biases (in fact “choices”) observed in the statistical chain enable us to identify the opportunities for professional autonomy: there are numerous negotiations involved in the construction of a representation of those “out of school”. The purpose of these school statistics is, at the central level, to inform and to support decision-making. At the local level, empirical everyday observation shows that they become a tool for the management of the school order and simultaneously an indicator of the activity of the administrators involved. Finally the reporting of absenteeism offers a space for stakes and games between school administrators and families who do not have the same capacities for “negotiating”. As a consequence, the struggle against non-attendance surreptitiously contributes to the reinforcement of school inequalities.